2020
DOI: 10.1186/s13005-020-00245-z
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive 3D analysis of condylar morphology in adults with different skeletal patterns – a cross-sectional study

Abstract: Background The correlation between individuals’ condylar morphology and their skeletal pattern is of great interest for treatment strategies ranging from orthodontic orthopaedics to orthognathic surgery. The objective of the present study was to investigate this relationship three-dimensionally. Methods A total of 111 adult patients (mean age = 27.0 ± 10.2 years) who underwent head computed tomography or cone beam computed tomography scans were included. Based on these data, 3D models of the skull and the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“… 20 Few other researchers have used a plane parallel to the Frankfurt horizontal passing through the most caudal point of the mandibular notch. 21 , 22 It noteworthy that the volume of the condyle is approximately 3 to 4 times greater with the former method when compared to the latter method because of the difference in the boundaries of segmentation.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Few other researchers have used a plane parallel to the Frankfurt horizontal passing through the most caudal point of the mandibular notch. 21 , 22 It noteworthy that the volume of the condyle is approximately 3 to 4 times greater with the former method when compared to the latter method because of the difference in the boundaries of segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…The literature showed that, during mandibular dynamics, there is a functional remodeling response [31]. In particular, the head of the mandibular condyle may react directly or indirectly to the load exerted by the chewing muscles [32]; it varies in thickness and mineralization in relation to different vertical facial models [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, the results were in the same direction because the subjects with skeletal class III showed a lower mandibular plane and a posterior condylar position. Some authors [21][22][23][24] observed a relation between the skeletal class and the sagittal and coronal position of the condyle, indicating that this morphology could explain the differences in the adaptive biomechanical patterns of the TMJ for different facial morphologies.…”
Section: Discussionmentioning
confidence: 99%